2013
DOI: 10.1089/jop.2012.0141
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Mitigates Rat Retinal Ischemic Injury: The Roles of Matrix Metalloproteinase-9, Inducible Nitric Oxide, and Heme Oxygenase-1

Abstract: Purpose: Retinal ischemia-associated ocular disorders, such as retinal occlusive disorders, neovascular agerelated macular degeneration, proliferative diabetic retinopathy, and glaucoma are vision-threatening. In this study, we examined whether and by what mechanisms resveratrol, a polyphenol found in red wine, is able to protect against retinal ischemia/reperfusion injury. Methods: In vivo rat retinal ischemia was induced by high intraocular pressure (HIOP), namely, 120 mmHg for 60 min. The mechanism and mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 32 publications
5
35
0
5
Order By: Relevance
“…A combination of single compounds or TCM combinations [24] might produce combined drug efects to the commercial agents due to their diferent treatment mechanisms with less complications. As described previously [9,[11][12][13][14][15]17], baicalein seems to have protective efect via antioxidation, antiapoptosis, HO-1upregulation and downregulation of HIF-1α, VEGF, and/or MMP-9. Furthermore, the underlying mechanism of the baicalein inhibition on retinal ischemia-induced upregulated MMP-9 level seems to be only ''in part'' associated with its anti-oxidative efect [13].…”
Section: Resveratrol Related To Mmp and Otherssupporting
confidence: 61%
See 2 more Smart Citations
“…A combination of single compounds or TCM combinations [24] might produce combined drug efects to the commercial agents due to their diferent treatment mechanisms with less complications. As described previously [9,[11][12][13][14][15]17], baicalein seems to have protective efect via antioxidation, antiapoptosis, HO-1upregulation and downregulation of HIF-1α, VEGF, and/or MMP-9. Furthermore, the underlying mechanism of the baicalein inhibition on retinal ischemia-induced upregulated MMP-9 level seems to be only ''in part'' associated with its anti-oxidative efect [13].…”
Section: Resveratrol Related To Mmp and Otherssupporting
confidence: 61%
“…In addition, Chi Ju Di Huang Wan (CJDHW), a "vision preserved" TCM combination, was demonstrated to protect against retinal ischemia through the atenuation of apoptosis, increase of antioxidative activity, downregulation of MMP-9, and inhibition of p38 mitogen-activated protein kinase (MAPK) [7]. Besides, eicient components of beverages, such as epigallocatechin-3-gallate [18] in green tea and resveratrol [15] in red wine, were also reported to possess protective efect on retinal ganglion cells injured after optic nerve axotomy and retinal ischemia, respectively. This review aimed at evaluating the efects of the following compounds or TCM combinations on retinal ischemia and their relations to MMPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Chen and colleagues evaluated RSV‐induced mitochondrial biogenesis in retinal ganglion cell line RGC‐5. In this study, the authors have shown evidence about the role of RSV to attenuate serum deprivation‐induced elicited RGC‐5 cell death through the SIRT‐1‐dependent PGC‐1α subcellular translocation; therefore, they suggested promoting mitochondrial biogenesis in order to mitigate glaucomatous retinopathy (Liu et al., 2013). …”
Section: Resveratrol and Diseasesmentioning
confidence: 99%
“…49 Suppression of MMP-2 and MMP-9 was also demonstrated in rats with ethinylestradiol-induced intrahepatic cholestasis of pregnancy 50 and in the retina of rats with high intraocular pressure-induced retinal ischemia. 51 In contrast to its effects on MMPs in tumour cells or in response to inflammation and ischemia, other studies have shown that resveratrol increases MMP secretion. 52 In one of our recent studies, topical application of resveratrol in rats pretreated with dexamethasone resulted in increased MMP-2 levels in the aqueous humor of rat eyes.…”
Section: Introductionmentioning
confidence: 99%